Correlation between A Body Shape Index and Target Organ Injury of Hypertension - LI Fangtang; YANG Xiaoli; CHEN Ruidan; YANG Yongjian (Xiehe Yixue Zazhi, 2022)
Objective  To explore the correlation between a body shape index (ABSI) and target organ injury in patients with hypertension.  Methods  A cross-sectional study was used to collect related clinical indicators of patients with hypertension who were hospitalized in the Department of Cardiology, Daping Hospital, Third Military Medical University from March 2020 to January 2021. ASBI quantile method was used to divide the patients into low ASBI group, medium ASBI group and high ASBI group. Multiple Logistic regression was used to analyze the correlation between ASBI and target organ injury in patients with hypertension.  Results  A total of 685 patients with hypertensive meeting the inclusion and exclusion criteria were enrolled, of which 445 had target organ damage; 229 cases were in the low ASBI group (ABSI≤0.076), 228 cases were in the medium ASBI group (0.076 < ABSI≤0.078), 228 cases were in the high ASBI group (ABSI > 0.078). The detection rate of left ventricular hypertrophy in the high ASBI group was higher than that in the low ASBI group(27.63% vs. 12.66%, P < 0.001). The detection rates of carotid atherosclerosis, and renal function impairment of the high ASBI group were higher than those of the medium ASBI group(39.04% vs. 26.32%, P=0.015;14.04% vs. 5.26%, P=0.007) and low ASBI group(39.04% vs. 25.76%, P=0.008;14.04% vs. 2.62%, P < 0.001). The multivariate Logistic regression analysis showed that ABSI was associated with increased left ventricular hypertrophy (OR=2.08, 95% CI: 1.24-3.50, P < 0.001) and renal injury (OR=6.47, 95% CI: 2.53-16.54, P < 0.001) in hypertensive patients.  Conclusion  The increased ABSI is related to the prevalence of left ventricular hypertrophy and renal damage in hypertensive patients.